Immune Thrombocytopenia Induced by Immune Checkpoint Inhibitors in Solid Cancer: Case Report and Literature Review - Liu, Xiaolin; Liang, Xiuju; Liang, Jing; Li, Yan; Wang, Jun (Frontiers in Oncology, 2020)
Immune checkpoint inhibitors, including antibodies targeting programmed cell death protein-1 (PD-1) and its receptor programmed cell death ligand-1 (PD-L1), represent promising therapeutic strategies for advanced human malignancies. However, a subgroup of patients will experience various autoimmune toxicities, termed as immune-related adverse events (irAEs), that occur as a result of on-target and off-tumor autoimmune response. Although irAEs are generally confirmed to be less severe than toxicities caused by conventional chemotherapy and targeted therapy, uncommon irAEs such as immune thrombocytopenia may occur with a very low incidence and sometimes be severe or fatal. This review focused on the epidemiology, clinical presentation and prognosis of immune thrombocytopenia occurring in advanced cancer patients induced by immune checkpoint inhibitors, especially in those with PD-1 or PD-L1 inhibitor treatment. We also firstly presented one patient with non-small cell lung cancer who received PD-L1 inhibitor durvalumab and develop severe thrombocytopenia.